Interdisciplinary Assessment of Hygiene Practices in Multiple Locations: Implications for COVID-19 Pandemic Preparedness in Vietnam - Nguyen, Trang Huyen Thi (Frontiers Media S.A., 2022)
10.3389/fpubh.2020.589183